2022
DOI: 10.3390/molecules28010146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanism of Quercetin in the Treatment of Experimental Colitis Using Network Pharmacology Analysis

Abstract: Quercetin, a flavonoid that is present in vegetables and fruits, has been found to have anti-inflammatory effects. However, the mechanism by which it inhibits colitis is uncertain. This study aimed to explore the effect and pharmacological mechanism of quercetin on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC). Mice were given a 4% (w/v) DSS solution to drink for 7 days, followed by regular water for the following 5 days. Pharmacological mechanisms were predicted by network pharmacology. High-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Each well was given the medication for 24 h before the addition of 10 μL CCK-8 reagent and an additional hour of incubation. The aforementioned test was carried out three times [ 33 ]. It was found that 500, 250, 125, 62.5, 31.25, and 15.625 μM of hordenine had no significant effect on the survival rate of MCEC cells for 24 h. Therefore, 500 μM was chosen as the hordenine administration condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each well was given the medication for 24 h before the addition of 10 μL CCK-8 reagent and an additional hour of incubation. The aforementioned test was carried out three times [ 33 ]. It was found that 500, 250, 125, 62.5, 31.25, and 15.625 μM of hordenine had no significant effect on the survival rate of MCEC cells for 24 h. Therefore, 500 μM was chosen as the hordenine administration condition.…”
Section: Methodsmentioning
confidence: 99%
“…All mice were then randomly divided into six groups ( n = 10/group): untreated control, DSS model, DSS+5-ASA 40 mg/kg, and DSS+hordenine 50 mg/kg, DSS+hordenine 25 mg/kg, DSS+hordenine 12.5 mg/kg ( Figure 1 B). Except for the control group, mice were given 4% ( w / v ) DSS solution for 7 days before being given regular water for the next 5 days [ 33 ]. From day 1 to day 12, mice in the treatment groups were administered 5-ASA or hordenine daily by gavage, while mice in control and DSS model groups were administered normal saline.…”
Section: Methodsmentioning
confidence: 99%